Disability Inclusive Employment Opportunity: Experiences of Deaf Young Adults - Harahap, Nur Hayati; Cabatay, Mulina M; Azizah, Nur (Universitas Negeri Yogyakarta, 2024)
A person with a disability has a higher risk of experiencing limited opportunities for employment and a higher rate of poverty. Deaf children are considered persons with disability, they are children with special needs characterized by loss of hearing function. In terms of deaf children's transition from school to the workplace, there's a necessity for them to gain vocational skills. Thus, teachers play an important role in providing support and mentoring to deaf children in determining their goals for college or work. This study aimed to describe how the transition process of deaf children from school to the workplace including the support they received from their teachers at school. This research used a qualitative descriptive approach. The main subjects of this research were deaf young adults who are currently employed at Sunyi Coffee. Data was collected through in-depth interviews and observations. In terms of data analysis, data reduction, data display, and generating a conclusion. The research findings showed that the two subjects have differences in the process of their transitioning from school to the workplace. The first subject received vocational training that matched his interest but applied to various types of jobs. The second subject's vocational training was not matched his interest but found a job that is suitable for his training.